PENERAPAN PRINSIP “THE BEST INTEREST OF THE CHILD” PADA KEHIDUPAN ANAK YANG TERPAKSA BEKERJA DI INDONESIA - Evans Angokaming Djehadut; Ni Putu Purwanti (Kertha Negara : Journal Ilmu Hukum, 2013)
The presence of children who are forced to work in Indonesia creates rulesgoverning restrictions on what jobs that can be done and in what jobs the children wereforbidden to work. Related to the principle of "the best interest of the child" which is theprimacy of the interests of the child, whether the principle of the protection of children whoare forced to work. Therefore, this article will explain what exactly is the purpose of theprinciple of "the best interest of the child" in the CRC (Convention on the Rights of theChild) and its application for children who are forced to work in Indonesia. In addition,this paper also describes a right or obligation if a child is forced to work.